2010
DOI: 10.1002/cne.22359
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortical inputs to the basal amygdala undergo pruning during late adolescence in the rat

Abstract: Transformations in affective and social behaviors, many of which involve amygdalar circuits, are hallmarks of adolescence in many mammalian species. In this study, using the rat as a model, we provide the first evidence that afferents of the basal amygdala (BA) undergo significant structural remodeling during adolescence. We used quantitative tract-tracing and gene expression profiling methods to characterize changes in the medial prefrontal cortical (mPFC) inputs to the BA across ages analogous to the late ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 59 publications
9
102
0
Order By: Relevance
“…Other studies have suggested a decrease in neuropil volume in the medial amygdala during puberty in the rat (Zehr et al, 2006). Similarly, a tracttracing study, using both retrograde and anterograde tracers, has shown that mPFC projections to the basal and accessory basal nuclei decrease between P25 and P90 in rats (Cressman et al, 2010).…”
Section: Second Stage: Myelinationmentioning
confidence: 82%
“…Other studies have suggested a decrease in neuropil volume in the medial amygdala during puberty in the rat (Zehr et al, 2006). Similarly, a tracttracing study, using both retrograde and anterograde tracers, has shown that mPFC projections to the basal and accessory basal nuclei decrease between P25 and P90 in rats (Cressman et al, 2010).…”
Section: Second Stage: Myelinationmentioning
confidence: 82%
“…In addition, BLA activity also facilitates extinction (Schroeder and Packard, 2003, 2004). As the PFC innervates the BLA by 28 and 45 days (Cressman et al, 2010), elevated D1 in the plPFC could facilitate extinction by modulating the BLA. D1 enhancement of the function of these connections could increase extinction in the juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pronounced structural remodeling of subcortical-prefrontal connections (eg myelination, synaptic pruning) that occurs during adolescence is likely to contribute to these qualitative shifts in fear expression (Somerville and Casey, 2010;Spear, 2000). For example, there is substantial pruning of neurons projecting from the IL to the basal amygdala from adolescence to adulthood (Cressman et al, 2010). Changes in connectivity between both the amygdala and the hippocampus, and the IL and PL during adolescence may initiate the shift from the restricted subcortical circuitry governing fear learning in juvenile stages, toward the more flexible and expansive circuit for fear regulation that is evident in adulthood.…”
Section: Developmental Changes In Fear-learning Circuitsmentioning
confidence: 99%